Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

The global role of bioassessment in policy delivery and decision-making for inland waters - Martyn G. Kelly; Gary Free; John P. Simaika; Stuart Warner; Andreas Bruder; Alejandra Correa-Bedoya; Fabio de Oliveira Roque; Tor Erik Eriksen; Jennifer Lento; Craig R. Macadam; Kristian Meissner; Marcelo S. Moretti; et al. (Journal of Environmental Management, 2025)

Short-chain PFAS perinatal exposure induces cognitive dysfunction and glial activation in adult rats - G. Foiani; M. Moretti; C. Zanardello; M. Sannia; E. Melchiotti; A. Vitola; F. Gallocchio; L. Lorenzini; L. Giardino; F. Mutinelli; L. Calzà; M. Vascellari (Journal of Comparative Pathology, 2025)

Mössbauer spectroscopy: a key tool to quantify Fe-speciation and distribution in H2-generating rocks - U. Geymond; K. Loiseau; V. Roche; G. Pasquet; S. Revillon; M. Sougrati; I. Moretti (Applied Geochemistry, 2025)

Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

DNA damage in workers exposed to pigment grade titanium dioxide (TiO2) and association with biomarkers of oxidative stress and inflammation - Sa. Bonetta; M. Macrì; M. Acito; M. Villarini; M. Moretti; Si. Bonetta; D. Bosio; G. Mariella; V. Bellisario; E. Bergamaschi; E. Carraro (Environmental Toxicology and Pharmacology, 2024)

Feline injection-site sarcomas (FISSs): could the assessment of tumour-infiltrating lymphocytes (TILs) help in prog-nostic evaluations? - I. Porcellato; E. Treggiari; V. Gismondi; I. Di Matteo; C. De Feo; G. Moretti; P. Roccabianca; E. Lepri; M. Sforna; C. Brachelente (Journal of Comparative Pathology, 2023)

Sex-dependent modulation of caerulein-induced acute pancreatitis in C57BL/6J mice: histopathological and immunohistochemical characterization - L. Bertola; G. Pepe; A. Dolce; A. Cappelleri; S. Canesi; P. Moretti; A. Giordano; E. Scanziani; E. Vegeto; C. Recordati (Journal of Comparative Pathology, 2023)

Sedimentological features of asbestos cement fragments in coastal environments (Taranto, southern Italy) - S. Lisco; I. Lapietra; R. Laviano; G. Mastronuzzi; T. Fracchiolla; M. Moretti (Marine Pollution Bulletin, 2023)

Experimental assessment of an indirect method to measure the post-combustion flue gas flow rate in waste-to-energy plant based on multi-point measurements - G. Bellani; L. Lazzarini; A. Dal Pozzo; S. Moretti; M. Zattini; V. Cozzani; A. Talamelli (Waste Management, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy) - I Lapietra; S Lisco; G Mastronuzzi; S Milli; C Pierri; F Sabatier; G Scardino; M Moretti (Journal of Earth System Science, 2022)

Early nitrogen supply as an alternative management for a cover crop-maize sequence under a no-till system - Letusa Momesso; Carlos A. C. Crusciol; Rogério P. Soratto; Carlos A. C. Nascimento; Ciro A. Rosolem; Luiz G. Moretti; Eiko E. Kuramae; Heitor Cantarella (Nutrient Cycling in Agroecosystems, 2021)
Optimizing agronomic efficiency (AE) of nitrogen (N) fertilizer use by crops and enhancing crop yields are challenges for tropical no-tillage systems since maintaining crop residues on the soil surface alters the nutrient supply to the system. Cover crops receiving N fertilizer can provide superior biomass, N cycling to the soil and plant residue mineralization. The aims of this study were to (i) investigate N application on forage cover crops or cover crop residues as a substitute for N sidedressing (conventional method) for maize and (ii) investigate the supply of mineral N in the soil and the rates of biomass decomposition and N release. The treatments comprised two species, i.e., palisade grass [ Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster] and ruzigrass [ Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins], and four N applications: (i) control (no N application), (ii) on live cover crops 35 days before maize seeding (35 DBS), (iii) on cover crop residues 1 DBS, and (iv) conventional method (N sidedressing of maize). The maximum rates of biomass decomposition and N release were in palisade grass. The biomass of palisade grass and ruzigrass were 81 and 47% higher in N application at 35 DBS compared with control in ruzigrass (7 Mg ha −1 ), and N release followed the pattern observed of biomass in palisade and ruzigrass receiving N 35 DBS (249 and 189 kg N ha −1 ). Mineral N in the soil increased with N application regardless of cover crop species. Maize grain yields and AE were not affected when N was applied on palisade grass 35 DBS or 1 DBS (average 13 Mg ha −1 and 54 kg N kg −1 maize grain yield) compared to conventional method. However, N applied on ruzigrass 35 DBS decreased maize grain yields. Overall, N fertilizer can be applied on palisade grass 35 DBS or its residues 1 DBS as a substitute for conventional sidedressing application for maize.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The longer the conditioning, the better the quality? The effects of leaf conditioning time on aquatic hyphomycetes and performance of shredders in a tropical stream - Cinthia G. Casotti; Walace P. Kiffer; Larissa C. Costa; Pâmela Barbosa; Marcelo S. Moretti (Aquatic Ecology, 2019)

Infection incidence, kernel colonisation, and mycotoxin accumulation in durum wheat inoculated with Fusarium sporotrichioides, F. langsethiae or F. poae at different growth stages - L. Nazari; E. Pattori; S. Somma; V. Manstretta; C. Waalwijk; A. Moretti; G. Meca; V. Rossi (European Journal of Plant Pathology, 2019)

Monitoring of ochratoxin A and ochratoxin-producing fungi in traditional salami manufactured in Northern Italy - C. Merla; G. Andreoli; C. Garino; N. Vicari; G. Tosi; M. L. Guglielminetti; A. Moretti; A. Biancardi; M. Arlorio; M. Fabbi (Mycotoxin Research, 2018)

Ant community in natural fragments of the Brazilian wetland: species–area relation and isolation - Rafael G. Cuissi; Chaim J. Lasmar; Tamara S. Moretti; Fernando A. Schmidt; Wedson D. Fernandes; Andreia B. Falleiros; José H. Schoereder; Carla R. Ribas (Journal of Insect Conservation, 2015)

Geochemical and isotopic insights into the assembly, evolution and disruption of a magmatic plumbing system before and after a cataclysmic caldera-collapse eruption at Ischia volcano (Italy) - R. J. Brown; L. Civetta; I. Arienzo; M. D’Antonio; R. Moretti; G. Orsi; E. L. Tomlinson; P. G. Albert; M. A. Menzies (Contributions to Mineralogy and Petrology, 2014)

Selection of Multiple Umbrella Species for Functional and Taxonomic Diversity to Represent Urban Biodiversity - T. SATTLER; G. B. PEZZATTI; M. P. NOBIS; M. K. OBRIST; T. ROTH; M. MORETTI (Conservation Biology, 2014)
Surrogates, such as umbrella species, are commonly used to reduce the complexity of quantifying biodiversity for conservation purposes. The presence of umbrella species is often indicative of high taxonomic diversity; however, functional diversity is now recognized as an important metric for biodiversity and thus should be considered when choosing umbrella species. We identified umbrella species associated with high taxonomic and functional biodiversity in urban areas in Switzerland. We analyzed 39,752 individuals of 574 animal species from 96 study plots and 1397 presences of 262 plant species from 58 plots. Thirty‐one biodiversity measures of 7 taxonomic groups (plants, spiders, bees, ground beetles, lady bugs, weevils and birds) were included in within‐ and across‐taxa analyses. Sixteen measures were taxonomical (species richness and species diversity), whereas 15 were functional (species traits including mobility, resource use, and reproduction). We used indicator value analysis to identify umbrella species associated with single or multiple biodiversity measures. Many umbrella species were indicators of high biodiversity within their own taxonomic group (from 33.3% in weevils to 93.8% in birds), to a lesser extent they were indicators across taxa. Principal component analysis revealed that umbrella species for multiple measures of biodiversity represented different aspects of biodiversity, especially with respect to measures of taxonomic and functional diversity. Thus, even umbrella species for multiple measures of biodiversity were complementary in the biodiversity aspects they represented. Thus, the choice of umbrella species based solely on taxonomic diversity is questionable and may not represent biodiversity comprehensively. Our results suggest that, depending on conservation priorities, managers should choose multiple and complementary umbrella species to assess the state of biodiversity. Selección de Múltiples Especies Paraguas para la Diversidad Funcional y Taxonómica para Representar la Biodiversidad Urbana

Aspergillus section Nigri as contributor of fumonisin B 2 contamination in maize - A.F. Logrieco; M. Haidukowski; A. Susca; G. Mulè; G.P. Munkvold; A. Moretti (Food Additives & Contaminants: Part A, 2014)

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Analysis of the PKR-eIF2alpha phosphorylation homology domain (PePHD) of hepatitis C virus genotype 1 in HIV-coinfected patients by ultra-deep pyrosequencing and its relationship to responses to pegylated interferon-ribavirin treatment - F. Bolcic; M. Sede; F. Moretti; G. Westergaard; M. Vazquez; N. Laufer; J. Quarleri (Archives of Virology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Identification, mycotoxin risk and pathogenicity of Fusarium species associated with fig endosepsis in Apulia, Italy - A. Moretti; L. Ferracane; S. Somma; V. Ricci; G. Mulè; A. Susca; A. Ritieni; A.F. Logrieco (Food Additives & Contaminants: Part A, 2010)

Lipid-lowering drug use in Italian primary care: effects of reimbursement criteria revision - G. Trifirò; M. Alacqua; S. Corrao; S. Moretti; D. U. Tari; M. Galdo; A. P. Caputi; V. Arcoraci (European Journal of Clinical Pharmacology, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Use and safety profile of antiepileptic drugs in Italy - M. L. Iorio; U. Moretti; S. Colcera; L. Magro; I. Meneghelli; D. Motola; A. L. Rivolta; F. Salvo; G. P. Velo (European Journal of Clinical Pharmacology, 2007)

Quality of Primary Food Products as Affected by Climate Change - G. Savoini; V. M. Moretti (Veterinary Research Communications, 2006)

Mainshocks and aftershocks of the 2002 molise seismic sequence, southern Italy - C. Chiarabba; P. De Gori; L. Chiaraluce; P. Bordoni; M. Cattaneo; M. De Martin; A. Frepoli; A. Michelini; A. Monachesi; M. Moretti; G. P. Augliera; E. D'Alema; et al. (Journal of Seismology, 2005)

Potential role of SEN virus on liver enzyme abnormalities in patients positive for hepatitis C virus with or without HIV infection - E. Quiros-Roldan; F. Moretti; C. Torti; V. Tirelli; R. Stellini; S. Pirovano; G. Carosi; L. Imberti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Identification, incidence and characterization of Fusarium proliferatumon ornamental palms in Spain - J. Armengol; A. Moretti; G. Perrone; A. Vicent; J.A. Bengoechea; J. García-Jiménez (European Journal of Plant Pathology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Toxin Profile, Fertility and AFLP Analysis of Fusarium verticillioides from Banana Fruits - A. Moretti; G. Mulè; A. Susca; M.T. González-Jaén; A. Logrieco (European Journal of Plant Pathology, 2004)

Mitochondrial DNA Variability in Fusarium Proliferatum (Gibberella Intermedia) - M. Láday; G. Mulè; A. Moretti; Z. Hamari; Á. Juhász; Á. Szécsi; A. Logrieco (European Journal of Plant Pathology, 2004)

Mitochondrial DNA Diversity and Lineage Determination of European Isolates of Fusarium graminearum (Gibberella zeae) - M. Láday; Á. Juhász; G. Mulè; A. Moretti; Á. Szécsi; A. Logrieco (European Journal of Plant Pathology, 2004)

A Species-Specific PCR Assay Based on the Calmodulin Partial Gene for Identification of Fusarium Verticillioides, F. Proliferatum and F. Subglutinans - G. Mulè; A. Susca; G. Stea; A. Moretti (European Journal of Plant Pathology, 2004)

Recessive resistance genes against potyviruses are localized in colinear genomic regions of the tomato (Lycopersicon spp.) and pepper (Capsicum spp.) genomes - G. Parrella; S. Ruffel; A. Moretti; C. Morel; A. Palloix; C. Caranta (Theoretical and Applied Genetics, 2002)

Toxigenic Fusarium Species and Mycotoxins Associated with Maize Ear Rot in Europe - A. Logrieco; G. Mulè; A. Moretti; A. Bottalico (European Journal of Plant Pathology, 2002)

Relationships between Na + , K + ‐ATPase, sialic acid content and fluidity in rainbow trout density‐separated erythrocytes - E. Salvolini; L. Nanetti; N. Moretti; A. Vignini; D. Martarelli; A. Frontini; A. M. Santroni; G. Falcioni; L. Mazzanti (Journal of Fish Biology, 2002)
A correlation was found between membrane fluidity, sialic acid (SA) content and Na + , K + ‐ATPase activity in the rainbow trout Oncorhynchus mykiss erythrocyte membrane and this suggests that alterations in erythrocyte Na + , K + ‐ATPase activity might be caused by modified membrane fluidity through modified SA content.

Molecular tagging of the Am gene from Lycopersicon hirsutum f. glabratum PI 134417 using AFLP markers - G. Parrella; I. Hochu; K. Gebre-Selassié; P. Gognalons; A. Moretti; G. Marchoux; C. Caranta (Acta Physiologiae Plantarum, 2000)

Space Variations of Stress Along the Tyrrhenian Wadati-Benioff Zone - G. Bruno; I. Guerra; A. Moretti; G. Neri (Pure and Applied Geophysics, 1999)

Nimesulide and renal impairment - R. Leone; A. Conforti; E. Ghiotto; U. Moretti; E. Valvo; G. P. Velo (European Journal of Clinical Pharmacology, 1999)

Applicability of Aspecific Noninvasive Methods for Biomonitoring of Occupational Exposure to Deltamethrin: Preliminary Study Using an Animal Model - M. Moretti; M. Villarini; G. Scassellati-Sforzolini; R. Pasquini; S. Monarca (Archives of Environmental Contamination and Toxicology, 1997)

Molecular and Biochemical Characterization of Two Atypical Toxigenic Populations of Fusarium Camptoceras - G. Mule’; C. Altomare; A. Moretti; G. Perrone; A. Logrieco (Cereal Research Communications, 1997)

Beauvericin and Fusaproliferin: New Emerging Fusarium Toxins - A. Logrieco; A. Ritieni; A. Moretti; G. Randazzo; A. Bottalico (Cereal Research Communications, 1997)

Clustering of Toxigenic Fungi Determined by rDNA Sequences - G. Mulè; A. Moretti; C. Altomare; A. Logrieco (Cereal Research Communications, 1997)